Needle-free atrial transseptal access: A safe and reproducible alternative for left atrial catheterization - Alex D. Pacheco-Bouthillier, MD; Jorge Javier Miguel-González, MD; Adriana González-Martínez, MD, PhD; Anna G. Everding-Rodríguez, MD; Silvia S. Gómez-Delgadillo, MD; Ángel E. Chávez-Torres, MD; Angélica Fregoso-Sánchez, MD; Benigno Ferreira-Piña, MD; Óscar S. Lomelí-Sánchez, MD, MSc; Hugo E. Coutiño-Moreno, MD, PhD; Vitelio A. Mariona-Montero, MD (Heart Rhythm O2)
Background: Left atrial catheterization is a common procedure in electrophysiology labs to treat arrhythmogenic substrates on the left side of the heart. Needle transseptal puncture is the standard approach, but it can lead to complications related to device design or operator technique. To reduce these complications, needle-free alternatives have been explored. Objective: This study aims to report the first multicenter application of the needle-free transseptal access (NeFTA) approach, assessing its safety and efficacy in patients undergoing electrophysiological procedures. Methods: This retrospective, observational multicenter study evaluated the safety and efficacy of the NeFTA approach in patients undergoing ablation of left arrhythmogenic substrates across 3 electrophysiology centers in Mexico. NeFTA uses only a guidewire, without a needle or sharp guidewire. The sheath, with a dilator, is guided into the fossa ovalis under fluoroscopic guidance, using anterior force and clockwise torque to allow the guidewire to puncture the septum with minimal risk. Results: The NeFTA technique was used in 366 patients. Most sheaths were deflectable, with nondeflectable sheaths in 43.4% of cases. Left atrial access via NeFTA was successful in 96.18% of cases, with pericardial effusion as the only complication (0.55% rate). Conclusion: This technique was reproducible and safe, achieving successful access on the first or second attempt in 96.18% of cases, regardless of the operator.